A lysine at the C-terminus of an odorant-binding protein is involved in binding aldehyde pheromone components in two Helicoverpa species. - Ya-Lan Sun; Ling-Qiao Huang; Paolo Pelosi; Chen-Zhu Wang (PLoS ONE, 2013)
Odorant-binding proteins (OBPs) are soluble proteins, whose role in olfaction of insects is being recognized as more and more important. We have cloned, expressed and purified an OBP (HarmOBP7) from the antennae of the moth Helicoverpa armigera. Western blot experiments indicate specific expression of this protein in the antennae of adults. HarmOBP7 binds both pheromone components Z-11-hexadecenal and Z-9-hexadecenal with good affinity. We have also performed a series of binding experiments with linear aldehydes, alcohols and esters, as well as with other compounds and found a requirement of medium size for best affinity. The affinity of OBP7, as well as that of a mutant lacking the last 6 residues does not substantially decrease in acidic conditions, but increases at basic pH values with no significant differences between wild-type and mutant. Binding to both pheromone components, instead, is negatively affected by the lack of the C-terminus. A second mutant, where one of the three lysine residues in the C-terminus (Lys123) was replaced by methionine showed reduced affinity to both pheromone components, as well as to their analogues, thus indicating that Lys123 is involved in binding these compounds, likely forming hydrogen bonds with the functional groups of the ligands.